2011
DOI: 10.1242/dev.055236
|View full text |Cite
|
Sign up to set email alerts
|

Stage-specific signaling through TGFβ family members and WNT regulates patterning and pancreatic specification of human pluripotent stem cells

Abstract: The generation of insulin-producing β-cells from human pluripotent stem cells is dependent on efficient endoderm induction and appropriate patterning and specification of this germ layer to a pancreatic fate. In this study, we elucidated the temporal requirements for TGFβ family members and canonical WNT signaling at these developmental stages and show that the duration of nodal/activin A signaling plays a pivotal role in establishing an appropriate definitive endoderm population for specification to the pancr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
258
3
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 355 publications
(299 citation statements)
references
References 62 publications
15
258
3
4
Order By: Relevance
“…Because activin A-induced differentiation does not generate homogenous cell population (Supplementary information, Figure S1B), we used CD184 (also named CXCR4), a well-known definitive endoderm marker [4,[19][20][21], to sort the cell population and confirmed successful endoderm differentiation by RT-qPCR analysis (Supplementary information, Figure S1C). In addition to CD184, another report [20] used both CD184 and CD117 (also named c-KIT) to mark the definitive endoderm cell population. Interestingly, we found that CD184+ cells are almost always CD117+ in our differentiation system (Supplementary information, Figure S1D).…”
Section: Resultsmentioning
confidence: 99%
“…Because activin A-induced differentiation does not generate homogenous cell population (Supplementary information, Figure S1B), we used CD184 (also named CXCR4), a well-known definitive endoderm marker [4,[19][20][21], to sort the cell population and confirmed successful endoderm differentiation by RT-qPCR analysis (Supplementary information, Figure S1C). In addition to CD184, another report [20] used both CD184 and CD117 (also named c-KIT) to mark the definitive endoderm cell population. Interestingly, we found that CD184+ cells are almost always CD117+ in our differentiation system (Supplementary information, Figure S1D).…”
Section: Resultsmentioning
confidence: 99%
“…Indirect Immunofluorescence Staining-Monolayer culture immunostaining was performed as described previously (2). The following primary and secondary antibodies were used: mouse anti-OCT3/4 (BD Transduction Laboratories; 1:500), rabbit anti-SOX17 (Beta Cell Biology Consortium; 1:500), donkey anti-mouse Alexa Fluor 647 (Invitrogen; 1:800), and donkey anti-rabbit Alexa Fluor 488 (Jackson ImmunoResearch Laboratories; 1:800).…”
Section: Expression Vectors and Lentivirus Production-full-lengthmentioning
confidence: 99%
“…6B). Because Nodal⅐Gdf1 had a higher specific activity than Nodal and was independent of serum, we compared its potential with that of commercially available Nodal and Activin A to differentiate pluripotent human ES cells into DE (2). First, treatment of hESCs with only Wnt3a and basic FGF already resulted in the down-regulation of the pluripotency marker OCT4 and significant up-regulation of DE markers such as SOX17 (Fig.…”
Section: Purified Nodal⅐gdf1 Complex Has High Specific Activity In Sementioning
confidence: 99%
See 2 more Smart Citations